Letter (copy) : Proposed meeting on Spain - Citrine, Walter, 1887-1983
011-0047-001 Sit. Espagne 336 WMC/WJB/AC/950 International 1st September, 1937 Mr. G. Stolz, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Stolz, PROPOSITION MEETING ON SPAIN. I have your letter of 31st instant, in which you give copies of the communications from Comrade Caballero. With regard to holding a meeting of the I.F.T.U. General Council concerning the situation in Spain, I have no objection to offer, except that, for myself, it is a most awkward time. This afternoon I am leaving London for Norwich, in order to prepare for our annual Trades Union Congress, which opens on Monday, 6th September, and will last all the week. If the proposed meeting is held during next week, it will be absolutely impossible for me to leave the Congress and attend, but I would arrange for our Comrade Hicks to act as my substitute. There is very little time, in any case, to call the meeting, as the League Council opens on 10th September, and I am afraid it cannot be very representative, but on the other hand, I recognise the tremendous urgency of the matter, and we must leave no stone unturned to help our Spanish comrades. Of course, the meeting should be a joint one, with the L.S.I., similar to those in the past, and if it were held in Geneva it would be more efficacious than if it were held in another city. Incidentally, I should mention that during the Congress week there is to be a debate on Spain, when proposals similar to those put forward by Comrade Caballero will come up for consideration. Needless to say, there is bound to be very wide publicity given to the discussions, which will not be confined to our own frontiers. Representatives of the world press will be present. It will be a demonstration of solidarity with the Spanish Government, and will help our efforts to arouse public opinion, and thereby to influence Governments in favour of the great cause of our Spanish comrades. Yours faithfully, General Secretary 292/946/11/47